1989
DOI: 10.1111/j.1349-7006.1989.tb02332.x
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene Amplification in Squamous Cell Carcinoma of the Oral Cavity

Abstract: We have determined the prevalence of amplification of c‐myc, N‐myc, L‐myc, H‐ras, Ki‐ras, and N‐ras oncogenes in 23 cases of squamous cell carcinoma of the oral cavity, using Southern hybridization analysis of DNA extracted from the primary tumor tissues. Nick‐translated oncogene probes and oncogene inserts labeled to high specific activities were used. We observed a 5‐ to 10‐fold amplification of one or more of c‐myc, N‐myc, Ki‐ras and N‐ras oncogenes in 56% of the tumor tissue samples, with these oncogenes n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
4

Year Published

1990
1990
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(40 citation statements)
references
References 25 publications
2
34
0
4
Order By: Relevance
“…This in vitro carcinogenesis model, along with the ability to grow NHOK in cell culture, provides an ideal system to study the alterations in gene expression that accompany cancer progression in humans. Although several genes have been reported to be mutated or di erentially expressed in oral cancers (Tadokoro et al, 1989;Saranath et al, 1989;Kannan et al, 1994a,b), a much larger number of genes are likely to be involved in the transformation of oral epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…This in vitro carcinogenesis model, along with the ability to grow NHOK in cell culture, provides an ideal system to study the alterations in gene expression that accompany cancer progression in humans. Although several genes have been reported to be mutated or di erentially expressed in oral cancers (Tadokoro et al, 1989;Saranath et al, 1989;Kannan et al, 1994a,b), a much larger number of genes are likely to be involved in the transformation of oral epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Hybridisation, washing and autoradiography were carried out as previously described (Saranath et al, 1989). Hind (Table I).…”
Section: Subjectsmentioning
confidence: 99%
“…Recent studies from our laboratory have demonstrated the involvement of oncogenes in squamous cell carcinoma of the oral cavity, via amplification of myc and ras family genes (Saranath et al, 1989). A 5-10-fold amplification of Ki-ras was reported in 17% and 30%, respectively, of the oral cancer samples investigated.…”
mentioning
confidence: 99%
“…Chiba et al (1990) We have previously demonstrated that there is elevated expression of several oncogenes, (Ha-ras, Ki-ras, c-erbB-2 and c-myc) in the development of squamous cell carcinoma of the head and neck (Field et al, 1986(Field et al, , 1987(Field et al, , 1989(Field et al, , 1990Field, 1991). We have reported a correlation between elevated c-myc oncoprotein expression and poor prognosis (Field et al, 1989), but as yet there is no published evidence to demonstrate that amplification or point mutations of oncogenes are associated with the clinical outcome of these patients (Saranath, 1989;Rumsby et al, 1989;Sheng et al, 1990;Field et al, unpublished). Parada et al (1984) have previously reported co-operation between p53 tumour antigen and ras in cellular transformation.…”
mentioning
confidence: 99%